Molecular Interactions between Complement Factor H and Its Heparin and Heparan Sulfate Ligands - Perkins, Stephen J.; Fung, Ka Wai; Khan, Sanaullah (Frontiers in Immunology, 2014)
Complement Factor H (CFH) is the major regulator of the central complement protein C3b in the alternative pathway of complement activation. A molecular view of the CFH interaction with native heparan sulphate is central for understanding the mechanism for how surface-bound CFH interacts with C3b bound to host cell surfaces. Heparan sulphate is composed of sulphated heparin-like S-regions that alternate with desulphated NA-regions. Solution structural studies of heparin (equivalent to the S-regions) and desulphated heparan sulphate (the NA-regions) by scattering and ultracentrifugation showed that each structure was mostly extended and partially bent, but with greater bending and flexibility in the NA-regions compared to the S-regions. Their solution structures have been deposited in the Protein Data Bank. The largest heparan sulphate oligosaccharides showed more bent and flexible structures than those for heparin. A folded-back domain structure for the solution structure of the 20 domains in CFH was determined likewise. CFH binds to the S-regions but less so to the NA-regions of heparan sulphate. The bivalent interaction of CFH-heparin was observed by ultracentrifugation, and binding studies of CFH fragments with heparin-coated sensor chips. In common with other CFH interactions with its physiological and pathophysiological ligands, the CFH-heparin and CFH-C3b interactions have moderate µM dissociation constants KD, meaning that these complexes do not fully form in vivo. The combination of the solution structures and binding studies indicated a two-site interaction model of CFH with heparin at cell surfaces. By this, the bivalent binding of CFH to a cell surface is cooperative. Defective interactions at either of the two independent CFH-heparin sites reduce the CFH interaction with surface-bound C3b and lead to immune disorders.